Mathematical Simulation of Transient Parameters of Vertical Grounding Electrodes - D. A. Gerasimovich; A. A. Dziaruhina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a mathematical simulation of transient parameters of vertical grounding electrodes for the first and subsequent short strokes of a lightning current. Results of the research show that transient resistances of grounding electrodes change appreciably in time. The transient resistances are always higher in the moment of voltage maximum then in the moment of current maximum. The dependences of transient resistances on grounding electrode length at different ground conductivity and lightning current parameters (first and subsequent short strokes) are obtained in the paper. The paper proposes an approximate criterion for estimation of grounding electrode equivalent length at transient condition that considers short stroke parameters of the lightning current and ground conductivity.